Development and Implementation of Tennessee Nonresidential Buprenorphine Treatment Guidelines - Erica Schlesinger; Wesley Geminn; Kenneth C Hohmeier; Howard L Burley Jr (University of Minnesota Libraries Publishing, 2018)
Objective: To describe the recent legislation in Tennessee and subsequent development and implementation of state-wide buprenorphine treatment guidelines. Practice Innovation: In 2016, Tennessee began licensing office-based opioid treatment (OBOT) clinics. Due to initial licensing criteria, not all providers were required to be licensed with the Department of Mental Health and Substance Abuse Services (TDMHSAS). The gap in licensing made it difficult to ensure an appropriate standard of care was being met by all addiction treatment providers. Therefore, the state developed legislation that allowed for the creation of best practice guidelines to encompass all providers of buprenorphine in the state of Tennessee, not just the licensed OBOT clinics. The guidelines define what the standard of care should entail while treating this vulnerable addiction population. Results: Tennessee legislation granted the formation of a committee to create the Tennessee Nonresidential Buprenorphine Treatment Guidelines. The committee was comprised of physicians, pharmacists, lawyers, law enforcement, and state officials. The finalized guidelines were published and effective January 1, 2018, and adopted as policy by the boards of medical examiners, osteopathic examination, and pharmacy shortly thereafter. The guidelines are now enforceable by the boards and give them the ability to discipline physicians who practice outside the standard of care. Conclusion: Tennessee legislation provides a model for other states to take action in combating this opioid crisis by not only increasing access to addiction treatment, but increasing access to quality care.   Article Type: Commentary